The best suggestion is to manipulate the equation to get x out of the denominator. Since there's a single x in the denominator, muliply both sides of the equation by x. Then solve as you would any simple algebraic equation.
Here, I might as well do it:
x^2 + 6 +10x = 9x/11
Collect terms, put in standard form and
factor, complete the square, or use the quadratic formula.
2007-05-16 06:21:53
·
answer #1
·
answered by modulo_function 7
·
0⤊
1⤋
Multiply x+10 and 11 on both sides:
11(x+6)=9(x+10)
11x+66=9x+90
2x=24
x=12
Check:
(12+6)/(12+10)=18/22 which can be reduced to 9/11
2007-05-16 06:29:55
·
answer #2
·
answered by Cool Nerd At Your Service 4
·
0⤊
0⤋
Solve the "x" variable in the equation.
(x+6/x+10)=(9/11)
First: eliminate fractions within an equation - multiply the denominators with both sides.
(11)(x+10)(x+6/x+10)=(11)(x+10)(9/11)
Sec: cross cancel "like" terms & combine the rest.
(11)(x+6)=(x+10)(9)
11(x)+11(6) = 9(x)+9(10)
11x+66 = 9x+90
Third: combine "like" terms - subtract 9x from both sides (when you move a term to the opposite side, always use the opposite sign).
11x-9x+66 = 9x-9x+90
2x+66 = 90
*Subtract 66 frm both sides.
2x+66-66 = 90-66
2x = 24
Fourth: divide both sides by 2.
2x/2 = 24/2
x = 12
2007-05-16 06:32:40
·
answer #3
·
answered by ♪♥Annie♥♪ 6
·
0⤊
0⤋
x + 6/x + 10 = 9 / 11
The means are 9(x + 10)
The extremes are 11(x + 6)
9(x + 10 = 11(x + 6)
9x + 90 = 11x + 66
9x + 90 - 9x = 11x + 66 - 9x
90 = 2x + 66
90 - 66 = 2x + 66 - 66
24 = 2x
24 / 2 = 2x / 2
24/2 = x
12 = x
- - - - - - - - - - -s-
2007-05-16 06:46:02
·
answer #4
·
answered by SAMUEL D 7
·
0⤊
0⤋
multiply throughout by 11x to get rid of the denominators.
You'll end up with a quadratic which can be solved.
NOTE: make sure you don't get x = 0 as a solution, then you have a problem. That's because you multiplied throughout by x.
You might be best writing the equation in the form:
[11x^2 + 101x + 66 ] / x = 0
That's the more accurate way of doing it, although in this case it does not make a difference.
Now solve the numerator to get
x = -0.708 , -8.474
2007-05-16 06:26:53
·
answer #5
·
answered by Dr D 7
·
0⤊
1⤋
Cross multiply:
11(x+6)=9(x+10) multiply through and solve for x.
This is all the help you are getting. If you can't get it from here you need to ask your teacher for additional tutoring.
2007-05-16 06:26:28
·
answer #6
·
answered by Randysaurus 3
·
0⤊
3⤋